The effectiveness of distance Arabic learning for Indonesian speakers using YouTube channels - Bahruddin, Uril; Ritonga, Mahyudin; Faruq, Muh.; Ramadhan, Muhammad Fadli (Journal of Education and Learning (EduLearn), 2024)
Online Arabic learning presents several challenges, one of which is the ineffective utilization of learning media. This study aims to describe the tendency of Arabic learners through the Dars Arabi YouTube channel video media and the relationship between the learner's propensity and the variables of gender, age, and educational background of Dars Arabi channel users. This study uses a descriptive statistical method. The sample selection was taken randomly from as many as 160 people from a population of around 17,800 YouTube channel subscribers. This study's findings indicate that the tendency of online Arabic learners is at a moderately average level. This study also shows no statistically significant difference between trends in YouTube channel users and the variables of gender, educational background, and users' age. This study's conclusion shows the importance of using YouTube media to learn Arabic with content that is fun and can be enjoyed by all groups of society in a relaxed manner.